COMPLEX QUALITY ASSESSMENT OF AQUATIC ECOSYSTEMS CONTAMINATED BY WASTEWATER DISCHARGES FROM THE AIRPORT - Франчук, Г. М.; Маджд, С. М.; Бондарук, А. В. (Science-based technologies, 2014)
State natural-territorial complexes nearby businesses operating and aircraft repair extremely critical. The main source of contamination of wastewater discharges airlines. Natural water contaminated with heavy metals, not recommended for use for domestic needs, technological processes, needs and fish farming. Thus, it is extremely important information about their concentration not only in the water column, but also in sediments, which are often one of the places of storage and disposal. Therefore, our research has focused on the assessment of surface water quality near the business of maintenance and repair of aviation equipment for example Nyvka River, which discharged wastewater airport "Kyiv" in Kyiv district Juliany. The article compared the different methods of water quality assessment and analysis of results. In this paper we presented methods: index of water pollution, contamination of the total index, a comprehensive assessment of water quality.